Heterologous biosynthesis of isobavachalcone in tobacco based on in planta screening of prenyltransferases - Guo, Lirong; Zhao, Wei; Wang, Yan; Yang, Yu; Wei, Cuimei; Guo, Jian; Dai, Jianye; Hirai, Masami Yokota; Bao, Aike; Yang, Zhigang; Chen, Haijuan; Li, Yimeng (Frontiers in Plant Science, 2022)
Isobavachalcone (IBC) is a prenylated chalcone mainly distributed in some Fabaceae and Moraceae species. IBC exhibits a wide range of pharmacological properties, including anti-bacterial, anti-viral, anti-inflammatory, and anti-cancer activities. In this study, we attempted to construct the heterologous biosynthesis pathway of IBC in tobacco (Nicotiana tabacum). Four previously reported prenyltransferases, including GuILDT from Glycyrrhiza uralensis, HlPT1 from Humulus lupulus, and SfILDT and SfFPT from Sophora flavescens, were subjected to an in planta screening to verify their activities for the biosynthesis of IBC, by using tobacco transient expression with exogenous isoliquiritigenin as the substrate. Only SfFPT and HlPT1 could convert isoliquiritigenin to IBC, and the activity of SfFPT was higher than that of HlPT1. By co-expression of GmCHS8 and GmCHR5 from Glycine max, endogenous isoliquiritigenin was generated in tobacco leaves (21.0 g/g dry weight). After transformation with a multigene vector carrying GmCHS8, GmCHR5, and SfFPT, de novo biosynthesis of IBC was achieved in transgenic tobacco T0 lines, in which the highest amount of IBC was 0.56 g/g dry weight. The yield of IBC in transgenic plants was nearly equal to that in SfFPT transient expression experiments, in which substrate supplement was sufficient, indicating that low IBC yield was caused by the low activity of SfFPT. Our research provided a prospect to produce valuable prenylflavonoids using plant-based metabolic engineering.